2019
DOI: 10.1016/j.pbi.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

SnRK1 activation, signaling, and networking for energy homeostasis

Abstract: The SnRK1 kinases are key regulators of the plant energy balance, but how their activity is regulated by metabolic status is still unclear. While the heterotrimeric kinase complex is well conserved between plants, fungi and animals, plants appear to have modified its regulation to better fit their unique physiology and lifestyle. The SnRK1 kinases control metabolism, growth and development, and stress tolerance by direct phosphorylation of metabolic enzymes and regulatory proteins and by extensive transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 69 publications
5
110
0
Order By: Relevance
“…This is in agreement with previous high-throughput verifications rates using an independent assay 5,48 and confirms that our curated Y2H interactions are of high quality. Additionally, these interactions occur in the nucleus, consistent with recent studies which have shown that SnRK1 relocates to the nucleus in response to stress 13,49 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with previous high-throughput verifications rates using an independent assay 5,48 and confirms that our curated Y2H interactions are of high quality. Additionally, these interactions occur in the nucleus, consistent with recent studies which have shown that SnRK1 relocates to the nucleus in response to stress 13,49 .…”
Section: Resultssupporting
confidence: 89%
“…SnRK1 complexes in vivo have been shown to include the α, β and βγ regulatory subunits, with the β subunits giving substrate specificity to the SnRK1 complex 13,20,22,32 . Of the 125 SnIPs identified, 48 were deemed core SnRK1 complex interactors (core SnIPs), as they partnered with at least one of the α catalytic subunits and one of the β/βγ regulatory subunits, increasing the confidence that these 184 SnRK1-SnIP HCI may be biologically relevant (Supplementary Data 4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumed ligands of the other CPuORFs in the network are unknown. metabolic enzymes during adaptation to a low-energy state (Crepin and Rolland, 2019). TOR responds to nutrient abundance by promoting ribosome biogenesis, cell cycle progression, and growth (Shi et al, 2018).…”
Section: Cpuorf Control Of the Plant Energy Signaling Networkmentioning
confidence: 99%
“…The signaling molecule trehalose-6-phosphate (T6P) inhibits SnRK1 activity (Crepin and Rolland, 2019). T6P is synthesized by T6P synthase from UDP-Glc and Glc-6-P and is metabolized by TPP to trehalose.…”
Section: Cpuorf Control Of the Plant Energy Signaling Networkmentioning
confidence: 99%